A rapid two-dimensional data collection system for the study of ferroelectric materials under external applied electric fields - Vergentev, Tikhon (Journal of applied crystallography, 2016)
Synchrotron X-rays on the Swiss Norwegian Beamline and BM28 (XMaS) at the ESRF have been used to record the diffraction response of the PMN-PT relaxor piezoelectric 67% Pb(Mg1/3Nb2/3)O3-33% PbTiO3 as a function of externally applied electric field. A DC field in the range 0-18 kV cm-1 was applied along the [001] pseudo-cubic direction using a specially designed sample cell for in situ single-crystal diffraction experiments. The cell allowed data to be collected on a Pilatus 2M area detector in a large volume of reciprocal space using transmission geometry. The data showed good agreement with a twinned single-phase monoclinic structure model. The results from the area detector were compared with previous Bragg peak mapping using variable electric fields and a single detector where the structural model was ambiguous. The coverage of a significantly larger section of reciprocal space facilitated by the area detector allowed precise phase analysis